New glycoconjugation strategies for Ruthenium(II) arene complexes via phosphane ligands and assessment of their antiproliferative activity - Iacopini, Dalila; Vančo, Ján; Di Pietro, Sebastiano; Bordoni, Vittorio; Zacchini, Stefano; Marchetti, Fabio; Dvořák, Zdeněk; Malina, Tomáš; Biancalana, Lorenzo; Trávníček, Zdeněk; Di Bussolo, Valeria (Bioorganic chemistry, 2022)
Glycoconjugation is a powerful tool to improve the anticancer activity of metal complexes. Herein, we modified commercial arylphosphanes with carbohydrate-derived fragments for the preparation of novel glycoconjugated ruthenium(II) p-cymene complexes. Specifically, d-galactal and d-allal-derived vinyl epoxides (VEβ and VEα) were coupled with (2-hydroxyphenyl)diphenylphosphane, affording the 2,3-unsaturated glycophosphanes 1β and 1α. Ligand exchange with [Ru(C2O4)(η6-p-cymene)(H2O)] gave the glycoconjugated complexes Ru1β and Ru1α which were subsequently dihydroxylated with OsO4/N-methylmorpholine N-oxide to Ru2β and Ru2α containing O-benzyl d-mannose and d-gulose units respectively. Besides, aminoethyl tetra-O-acetyl-β-d-glucopyranoside was condensed with borane-protected (4-diphenylphosphanyl)benzoic acid by HATU/DIPEA under MW heating, to afford the amide 3∙BH3. Zemplén deacylation with MeONa/MeOH gave the deprotected d-glucopyranoside derivative 4∙BH3. The glycoconjugated phosphane complexes Ru3 and Ru4 were obtained by reaction of the phosphane-boranes 3∙BH3 and 4∙BH3 with [Ru(C2O4)(η6-p-cymene)(H2O)]. The employed synthetic strategies were devised to circumvent unwanted phosphine oxidation. The compounds were purified by silica chromatography, isolated in high yield and purity and characterized by analytical and spectroscopic (IR and multinuclear NMR) techniques. The behaviour of the six glycoconjugated Ru complexes in aqueous solutions was assessed by NMR and MS measurements. All compounds were screened for their in vitro cytotoxicity against A2780/A2780R human ovarian and MCF7 breast cancer cell lines, revealing a significant cytotoxicity for complexes containing the 2,3-unsaturated glycosyl unit (Ru1β, Ru1α). Additional studies on five other human cancer cells, as well as time-dependent toxicity and cell-uptake analyses on ovarian cancer cells, confirmed the prominent activity of these two compounds - higher than cisplatin - and the better performance of the β anomer. However, Ru1β, Ru1α did not show preferential activity against cancer cells with respect to fetal lung fibroblast and human embryonic kidney cells as models of normal cells. The effects of the two ruthenium glycoconjugated compounds in A2780 ovarian cancer cells were further investigated by cell cycle analysis, induction of apoptosis, intracellular ROS production, activation of caspases 3/7 and disruption of mitochondrial membrane potential. The latter is a relevant factor in the mechanism of action of the highly cytotoxic Ru1β, inducing cell death by apoptosis.
Keywords: Ligands; Humans; ligandy; Cytotoxicity; Cell-cycle; komplexní sloučeniny; Mitochondrial membrane potential; Female; nádory vaječníků; Antineoplastic Agents; Ovarian Neoplasms; fosfiny; lidé; Coordination Complexes; Anticancer metal complexes; Ruthenium(II) arene; ženské pohlaví; ruthenium; Carbohydrate complexes; nádorové buněčné linie; protinádorové látky; Glycoconjugation; Cell Line, Tumor; Phosphines; Phosphane ligand; Ruthenium; Apoptosis